Preparation of a milk spoilage indicator adsorbed to a modified polypropylene film as an attempt to build a smart packaging - Cavallo, Jesica Anabel (2014)
A colorimetric sensor of milk spoilage was built from adsorption of methylene blue (MB) onto a modified polypropylene film (PP). First, acrylic acid (AA) was grafted onto PP surface by photograft polymerization reaction, and then either MB or chitosan chains (Cs) was attached to polyacrylic acid (PAA). Three syntheses were researched in order to fix MB to PP-g-PAA?Cs into different levels of PAA?Cs layers. The growth of microorganisms and the generation of reducing substances take place during milk decomposition, where MB is reduced to its colourless form. Binding stability of dye on the film and its redox activity were confirmed by UV?vis spectrophotometry. Reduction kinetics of MB shows a response fast enough to work as a spoilage indicator against samples of liquid milk in different preservation states. This performance also describes these devices as suitable sensors to be used in the development of smart packagings.